UNOS/OPTN Data-guided Assessment of Focal Segmental Glomerulosclerosis After Kidney Transplantation and Evaluation of Immunosuppressive Protocols in a Steroid-free Center. Issue 9 (5th August 2021) - Kurian, Sunil M.; Spierling Bagsic, Samantha R.; Case, Jamie; Barrick, Bethany L.; Schaffer, Randolph; Rice, James C.; Marsh, Christopher L.
Abstract : Background: Focal segmental glomerulosclerosis (FSGS) is a common recurrent glomerulopathy associated with graft loss and patient survival after kidney transplantation (KT). However, its natural history, clinical predictors, and treatment response are still poorly understood. Steroid withdrawal regimens in KT have been associated with improvements in cardiovascular risk and patient outcomes. The Scripps Center for Organ Transplantation (SCOT) uses a rapid low-dose steroid withdrawal immunosuppression (IS) protocol for KT maintenance. Methods: We assessed the impact of our protocol on FSGS disease recurrence over a 10-y period to reassess our steroid and IS protocols and to evaluate if our patient outcomes diverge from published data. We compared 4 groups: steroids always, steroid free, steroid switch on, and steroid weaned off. We used IS and induction-matched retrospective data from United Network for Organ Sharing (UNOS) to investigate patient and graft survival for FSGS at SCOT. Results: Our analysis results differ from earlier studies showing that FSGS was associated with a higher risk of graft loss, perhaps because of selection of a UNOS data set filtered to match the SCOT IS protocol for making direct comparisons. Overall outcomes of graft failure and recipient death did not differ between SCOT patients and steroid-free transplant patient data from the UNOS data for FSGS. SCOT recurrence rate for FSGS was 7.5%, which was lower than in most published single-center studies. Conclusions: Based on our results, we believe that it is safe to continue the steroid avoidance protocols at SCOT and the steroid-free protocol may not be detrimental when the adverse effects and toxicities associated with steroid use are considered.